Trabajo y familia: hacia una cultura familiar amigable en el contexto latinoamericano - Debeljuh, Patricia (2004)
The balance of work and family is the daily struggle of every person who must satisfy the often-conflicting demands of both spheres of his life. The absence of effective solutions to this problem not only affects the family but also companies through work absenteeism, low productivity, increased stress, among other effects. The working conditions of the future will have to resolve the tensions between old paradigms and new realities and create a culture that reflects the characteristics of the current workforce. To the extent that companies recognize and respond to the family needs of their employees, they will develop strategies to harmonize work and family life. The present study reviews these strategies and their gradual implementation, whose last stage is the creation of a friendly family corporate culture, the only area in which employees can achieve a work-personal balance.